LPA Gene Polymorphisms and Gene Expression Associated with Coronary Artery Disease - Song, Zi-Kai (Biomed Res Int, 2017)
The aim of our study was to investigate the influence of LPA gene polymorphisms for CAD risk and Lp(a) in a case-control study of Chinese Han population. In addition, we further analyzed the effect of LPA gene expression on plasma levels of Lp(a) and CAD risk. First, five SNPs (rs1367211, rs3127596, rs6415085, rs9347438, and rs9364559) in LPA gene were genotyped using the SEQUENOM Mass-ARRAY system in two groups. Second, we used quantitative real-time PCR to examine the mRNA expression levels of LPA gene in 92 cases and 32 controls. Results showed that the frequency of rs6415085-T allele was significantly higher in case group than that in control group (P < 0.05). Haplotypes were not associated with CAD risk (P > 0.05). And cases with the TT/TG genotype had significantly higher plasma Lp(a) levels compared with those that have the rs6415085 GG genotype (P < 0.05). Additionally, the mRNA expression levels in case group are significantly higher than that in control group (P < 0.05). Our study confirmed that rs6415085 was associated with CAD and increased plasma Lp(a) levels. And increased mRNA expression level of LPA gene may be a mechanism in development of CAD.